Molecular and functional characterization of choline transporter in the human trophoblastic cell line JEG-3 cells. Issue 6 (June 2015) - Yara, M.; Iwao, B.; Hara, N.; Yamanaka, T.; Uchino, H.; Inazu, M.
Abstract: Introduction: Choline is essential for the synthesis of the major membrane phospholipid phosphatidylcholine (PC), the methyl donor betaine and the neurotransmitter acetylcholine (ACh), which is involved in several vital biological functions that play key roles in fetal development. In this study, we examined the molecular and functional characteristics of choline uptake in the human trophoblastic cell line JEG-3. Methods: We examined [ 3 H]choline uptake in the human trophoblastic cell line JEG-3. The expression of CTL1 and CTL2 was evaluated by quantitative real-time PCR, western blotting and immunocytochemistry. Results: We demonstrated that JEG-3 cells take up [ 3 H] choline by a saturable process that is mediated by a Na + -independent and pH-dependent transport system. The cells have two different [ 3 H] choline transport systems, high- and low-affinity, with K m values of 28.4 ± 5.0 μM and 210.6 ± 55.1 μM, respectively. Cationic compounds and hemicholinium-3 (HC-3) inhibited choline uptake. Choline transporter-like protein 1 (CTL1) and CTL2 mRNA and protein were highly expressed in JEG-3 cells and were localized to the plasma membrane. Discussion: The present results suggest that choline is mainly transported via a high-affinity choline transport system (CTL1) and a low-affinity choline transport system (CTL2) in human trophoblastic JEG-3 cells. These transporters play an important role in the growth of the fetus. Graphical abstract: Highlights: Characteristics of choline transporters were examined in JEG-3 cells. Choline uptake is mediated by two transport systems (high- and low-affinity). CTL1 and CTL2 mRNA and protein were highly expressed in JEG-3 cells. Choline is mainly transported via both CTL1 (high-affinity) and CTL2 (Low-affinity).